2021
DOI: 10.32582/aa.62.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of benthic diatom community structures on natural and artificial substrates in marine lake (Adriatic Sea)

Abstract: In this study, the diatoms of three alternative habitats (epilithon, epiphyton and artificial sub-strate) were compared to understand the differences in composition on artificial and natural sub-strates. For this purpose, the samples were collected weekly between 11th August and 2nd Septem-ber 2016 at a sampling site in a shallow marine lake, Mrtvo More (Dead Sea) on Lokrum Island near Dubrovnik (South Adriatic, Croatia). In addition to detailed light microscopic analysis, ultrastructural analysis of benthic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Even though we enlarged the checklist for the phytoplankton of the eastern Adriatic coast with the here-reported results, we assume for methodological reasons that a part of the observable biodiversity still remains unknown. Several genera known as predominant benthic genera that are highly represented in phytoplankton checklists, such as Mastogloia , Licmophora or Synedra ( Car et al 2021 ), but are less likely to be found in a water column, were not represented in our metabarcoding results, which is probably a result of the sampling methodology, where we did avoid net hauls close to the sea floor. As described earlier, variable DNA extraction efficiencies between taxa due to different cell morphologies, for example, robust cell coverings, such as the diatom silica frustule, could potentially lessen extraction efficiency, leaving them undetected in metabarcoding efforts ( Maki et al 2017 ).…”
Section: Discussionmentioning
confidence: 96%
“…Even though we enlarged the checklist for the phytoplankton of the eastern Adriatic coast with the here-reported results, we assume for methodological reasons that a part of the observable biodiversity still remains unknown. Several genera known as predominant benthic genera that are highly represented in phytoplankton checklists, such as Mastogloia , Licmophora or Synedra ( Car et al 2021 ), but are less likely to be found in a water column, were not represented in our metabarcoding results, which is probably a result of the sampling methodology, where we did avoid net hauls close to the sea floor. As described earlier, variable DNA extraction efficiencies between taxa due to different cell morphologies, for example, robust cell coverings, such as the diatom silica frustule, could potentially lessen extraction efficiency, leaving them undetected in metabarcoding efforts ( Maki et al 2017 ).…”
Section: Discussionmentioning
confidence: 96%